The Role of Corporate Governance and Environmental Committees on Greenhouse Gas Disclosure - MANURUNG, Daniel T. H; HARDIKA, Andhika Ligar; HAPSARI, Dini W.; SEBAYANG, Minda Maulina (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018DO - 10.14505//jemt.v9.7(31).05, 2019)
The study aims to determine the impact of corporate governance (board of commissioners, directors and gender diversity) and environmental committees in greenhouse gas disclosure. The sampling method in this study using purposive sampling method with a total of 26 manufacturing companies listed in Indonesia Stock Exchange by using multiple regression analysis. The results show that the role of the board of commissioners has not been able to provide control over the reduction of greenhouse gases on the company, the board of directors has no effect on the disclosure of greenhouse gases refuse to make emission gas reduction due to litigation pressure and expenditure, gender diversity has not been able to control the role of women and men in decision-making and risk and environmental committees have been little able to contribute to the disclosure of greenhouse gases as it is expected that the establishment of an environmental committee on the company.